(3JaSjQ GdbQBfs - (3Ydj Hf YjSi Hf Ydj Hf YHO Gddg, CHh GdMSf GdQeGfj,J (B384 (3g` s
(3ChdgG (B:s
(3jHJOF HJajSQ bhdg JYGdi (B( (3jJLQYg hdG jcGO jSjZg hGJjg GdehJ ef cd ecGf (B) s
(3BNQgG (B:s
(3jfJgi HJbSjQ bhdg JYGdi (B( (3hONd LfJg hgh XGde (B) s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B447s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs